Neprodani in trdni. Ja, seveda, potem pa svizec --- - Polajnar, Janja (Jezik in slovstvo, 2013)
The article presents advertising slogans in Slovenian that are becoming independent or lexicalized, i.e., they are used in new, mostly non-advertising contexts. On the basis of a comparison of research found in Slovenian and German literature on advertising quotes and quotation idioms, a model for describing the gradual lexicalization of advertising slogans has been developed (ad hoc slogan permanent slogan quotation idiom). Selected examples in Slovenian illustrate the use of independent and dependent slogans promoting Slovenian and foreign trademarks, including their various forms,variants and modifications. There is also a brief treatment of phraseological slogan models.
Keywords: Slovene; slovenščina; phraseology; frazeologija; citati; izcitatni frazemi; frazeološki modeli; oglasi; oglasni slogani